12. CLINICAL AND PARACLINICAL CHARACTERISTICS OF PATIENTS WITH MAXILLOFACIAL INFECTION CAUSED BY DENTAL AT NGHEAN GENERAL FRIENDSHIP HOSPITAL IN 2022-2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe clinical and paraclinical characteristics of patients with maxillofacial infections caused by teeth treated at the Department of Maxillofacial, Nghe An General Friendship Hospital, in 2022-2024.Subject and methods: Cross-sectional descriptive study on 42 patients diagnosed and treated for maxillofacial infections caused by teeth at the Department of Maxillofacial, Nghe An General Friendship Hospital from January 2022 to March 2024. The study subjects had their medical history taken, clinical examination, and X-rays taken to record the research indicators.Results: The study subjects were mainly in the age group of 21-40, with a male/female ratio ≈ 1/1; the most common cause was from the dental pulp (66.7%), followed by periodontitis (28.6%) and periodontitis (4.7%). Clinically, the main signs of maxillofacial infections due to teeth were swelling (100%), pain (100%), lymphadenopathy (100%), limited mouth opening (80.1%), and fever (76.2%). Systemic diseases were very diverse, of which hypertension accounted for the highest rate at 23.8%, diabetes at 19%, hepatitis B or C (7.1%), and nasopharyngeal cancer (4.8%). Regarding the location of the infected spaces: the most common infected space is the buccal space (76.2%), followed by the submandibular space (33.3%), masseter muscle (6%), chin space, canine fossa, parotid space (7.1%), pterygomaxillary space (4.8%), sublingual space and temporal space (2.4%).Conclusion: Common accompanying systemic diseases are hypertension and diabetes. The infected cavity occurs in most locations of the maxillofacial region, of which the cheek cavity is the most infected cavity. The most common cause of infection is the dental pulp. The main clinical symptoms are swelling, pain, lymphadenopathy, and limited mouth opening.
Keywords: Maxillofacial infection caused by teeth; Nghe An General Friendship Hospital.